Synchrotron X-ray diffraction based method for stress intensity factor evaluation in the bulk of materials. (December 2018) - Lopez-Crespo, P.; Peralta, J.V.; Withers, P.J.
Highlights: New methodology for investigating the interior of engineering materials. Estimation of the stress intensity factor in the bulk of metal alloys. Hybrid approach combining experimental data and an elastic model describing the strain field surrounding the crack tip. Analytical model based on Williams' series development to describe the strain field around the crack tip. Experimental data measured in the bulk of the material with synchrotron X-ray diffraction. Abstract: A generalised approach for determining the stress intensity factor in the bulk of non-transparent materials is presented. The new approach combines experimental elastic strain data, measured with powerful synchrotron X-ray diffraction, with an elastic model based on Williams' series development. The stress intensity factor is calculated using a multi-point over-deterministic method where the number of experimental data points is higher than the number of unknowns describing the elastic field surrounding the crack-tip. The tool is tested on X-ray strain measurements collected on a bainitic steel. In contrast to surface techniques the approach provides insights into the crack tip mechanics deep within the sample and makes full use of the plastic zone data. Satisfactory results are obtained with 1 term in the series development and a smaller region of interest. By increasing the number of terms, it is possible to improve the accuracy in the SIF predictions but this requires a larger region of interest.